Alternative medicine consultations and remedies in patients with the irritable bowel syndrome. Issue 7 (July 1986) - Smart, H L; Mayberry, J F; Atkinson, M
Abstract : The use of alternative medicine was assessed by questionnaire in 96 patients with irritable bowel syndrome, 143 patients with organic upper gastrointestinal disorders and 222 patients with Crohn's disease of comparable age and sex. Significantly more patients with the irritable bowel syndrome (16%) had consulted practitioners of alternative medicine about their condition than had patients in either of the other groups. Similarly, significantly more irritable bowel syndrome patients said they would consult an alternative medicine practitioner (41%) if conventional treatment failed. Current usage of alternative medicine remedies was significantly greater in the irritable bowel syndrome patients (11%) than in patients with Crohn's disease (4%) and tended to be greater than in patients with organic upper gastrointestinal disorders (6%). This study has shown that the use of alternative medicine is common in patients with irritable bowel syndrome and this does not appear to be explicable in terms of the nature, chronicity or refractoriness to treatment of symptoms.